2009
DOI: 10.3390/wevj3030457
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Manufacturing Costs of Lithium-Ion Batteries for PHEVs

Abstract: In this study, we developed a model for calculating the costs of lithium-ion batteries supporting electric drive in light duty passenger vehicles (LDVs). The model calculates the annual materials requirements from design criteria for the battery pack including power, capacity, number of cells, and cell chemistry parameters. The costs of capital equipment, plant area and labor for each step in the manufacturing process were estimated for a baseline plant. These costs are adjusted for each battery pack studied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 2 publications
0
43
0
Order By: Relevance
“…This program, designated BatPaC, is the product of long-term research and development at Argonne through sponsorship by the U.S. Department of Energy [8][9][10][11][12][13][14][15][16]. The latest version, BatPaC v2.1, is available from the Argonne website (www.cse.anl.gov/batpac).…”
Section: Battery Modeling Methodsmentioning
confidence: 99%
“…This program, designated BatPaC, is the product of long-term research and development at Argonne through sponsorship by the U.S. Department of Energy [8][9][10][11][12][13][14][15][16]. The latest version, BatPaC v2.1, is available from the Argonne website (www.cse.anl.gov/batpac).…”
Section: Battery Modeling Methodsmentioning
confidence: 99%
“…Like the Prius plug-in, the prototype Ford Escape plug-ins use the same approach -make use of the existing electric machinery and control equipment as much as possible and increase the energy storage capacity of the pack significantly more than its power. Nelson et al (2009) and have shown that this approach offers a relatively inexpensive incremental cost for a PHEV.…”
Section: Light-duty Hybrids That Plug In Store Grid Electricity Andmentioning
confidence: 99%
“…Though very likely for a different chemistry than Nissan and NEC Corporation (a battery manufacturer) will use, at volumes of 200,000 packs per year, the model presented by Nelson et al (2009) estimates that NCA-G electric vehicle battery packs (energy-oriented packs with W/Wh ratios under 5) could cost less than $200/kWh for battery pack manufacturers to produce. It would be necessary for motor vehicle manufacturers to achieve this production cost so they would be able to offer packs at a price of approximately $240/kWh to consumers.…”
Section: According To Muller (2009)mentioning
confidence: 99%
See 1 more Smart Citation
“…Telephone conversations with various battery manufacturers yielded a current price of $700 to 1500/kWh, with the price for large volume sales of 1000 batteries or more in 5 years estimated at $600/kWh. Cost estimation models from Argonne National Laboratory (ANL), Tiaxx and The US Advanced Battery Consortium (USABC) (Nelson et al 2009, Barnett et al 2009, USCAR 2007, , when normalized to the same total energy, provided a cost of $440, 415 and 450/kWh respectively for large-volume production, or ~ $420/kWh. Taking the average of $600/kWh and $420/kWh, the cost to be used for this study was assumed to be $510/kWh long-term for high volume production.…”
Section: A12 Capital Costmentioning
confidence: 99%